Vertical accretion and sediment storage in oxbows and meander cutoffs on the Gatberg River Floodplain, Eastern Cape, South Africa - De Villiers, Zenaria Oriskia (Stellenbosch : Stellenbosch University, 2023)
Thesis (MA)--Stellenbosch University, 2023.